General anesthesia, conscious sedation, or nothing: Decision‐making by children during painful procedures. Issue 5 (3rd January 2019) - Maslak, Karolina; Favara‐Scacco, Cinzia; Barchitta, Martina; Agodi, Antonella; Astuto, Marinella; Scalisi, Rita; Italia, Simona; Bellia, Francesco; Bertuna, Gregoria; D'Amico, Salvatore; La Spina, Milena; Licciardello, Maria; et al.
Abstract: Background: Following diagnosis, children with cancer suddenly find themselves in an unknown world where unfamiliar adults make all the important decisions. Children typically experience increasing levels of anxiety with repeated invasive procedures and do not adapt to the discomfort. The aim of the present study is to explore the possibility of asking children directly about their medical support preferences during invasive procedures. Procedure: Each patient was offered a choice of medical support on the day of the procedure, specifically general anesthesia (GA), conscious sedation (CS), or nothing. An ad hoc assessment tool was prepared in order to measure child discomfort before, during, and after each procedure, and caregiver adequacy was measured. Both instruments were completed at each procedure by the attending psychologist. Results: We monitored 247 consecutive invasive procedures in 85 children and found that children in the 4 to 7 year age group showed significantly higher distress levels. GA was chosen 66 times (26.7%), CS was chosen 97 times (39.3%), and nothing was chosen 5 times and exclusively by adolescents. The child did not choose in 79 procedures (32%). The selection of medical support differed between age groups and distress level was reduced at succeeding procedures. Conclusions: Offering children the choice of medical support during invasive procedures allows for tailored support based on individual needs and is an effective modality to return active control to young patients, limiting the emotional trauma of cancer and treatment.